Children's eating behaviours and related constructs: conceptual and theoretical foundations and their implications - Alan Russell; Elena Jansen; Alissa J. Burnett; Jookyeong Lee; Catherine G. Russell (BMC, 2023)
Abstract Background There is a substantial body of research on children's eating behaviours (e.g., food responsiveness and fussiness) and related constructs (e.g., eating in the absence of hunger, appetite self-regulation). This research provides a foundation for understanding children's dietary intakes and healthy eating behaviours, as well as efforts at intervention, whether in relation to food avoidance, overeating and/or trajectories to excess weight gain. The success of these efforts and their associated outcomes is dependent on the theoretical foundation and conceptual clarity of the behaviours and constructs. This, in turn contributes to the coherence and precision of the definitions and measurement of these behaviours and constructs. Limited clarity in these areas ultimately creates uncertainty around the interpretation of findings from research studies and intervention programs. At present there does not appear to be an overarching theoretical framework of children's eating behaviours and associated constructs, or for separate domains of children's eating behaviours/constructs. The main purpose of the present review was to examine the possible theoretical foundations of some of the main current questionnaire and behavioural measures of children's eating behaviours and related constructs. Methods We reviewed the literature on the most prominent measures of children's eating behaviours for use with children aged ~ 0-12 years. We focused on the explanations and justifications for the original design of the measures and whether these included theoretical perspectives, as well as current theoretical interpretations (and difficulties) of the behaviours and constructs. Results We found that the most commonly used measures had their foundations in relatively applied or practical concerns rather than theoretical perspectives. Conclusions We concluded, consistent with Lumeng & Fisher (1), that although existing measures have served the field well, to advance the field as a science, and better contribute to knowledge development, increased attention should be directed to the conceptual and theoretical foundations of children's eating behaviours and related constructs. Suggestions for future directions are outlined.